SUBAK LAND INFORMATION SYSTEM BASED ON REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEM IN DENPASAR CITY - Indayati Lanya; Nengah Netera Subadiyasa; Jeremia Hutauruk (Geoplanning: Journal of Geomatics and Planning, 2017)
Subak in this paper is a unit of agricultural area, with names, have palemahan (paddy field resource), pawongan (human resources/farmers), and paddy field farming systems. Subak as local  genious  Bali, constructed since the 7th century, until now Subak system still exist in Denpasar. UNESCO, in 2011, rewarded Subak as a world cultural heritage. Ironically, not one district/city, and the Province of Bali has maps spatially Subak, they only have statistical data. The development era of technology and communications requires the ease and speed of getting data and the latest information with a high degree of spatial accuracy. The answer requires data base information based on information and communication technology (ICT). Worldview satellite imagery coverage of Denpasar in 2015, and ArcGIS 10.3 software used for mapping land and extensive rice fields of Subak (spatial data). Secondary data consists of land resources (LR), the primary data includes the name pekaseh delineation and  area subak, human resources (HR) and agricultural activities were used as attribute data. Denpasar City has 41  Subak  in 2015,  Subak area on the analysis of satellite imagery (2008.6 ha) was smaller (520.4 ha) than the Central Statistics Agency (CSA, Denpasar  2529 ha), with r2 = 0.8967. Soil fertility moderate, land suitability agro-ecosystem very suitable (S1) for  rice  field and suitable (S2) for second crops and horticulture lowlands, required land cultivation and fertilization, suitable to crop needs. HR status of farmers as cultivators 72% and Landowners 28%.Subak paddy crop rotation pattern Denpasar City is paddy-paddy/palawija–palawija/paddy. The data base is composed of a map Subak Subak (spatial data), the data  LR,  HR and agricultural activities (attributes data).